Presentation of antigen on extracellular vesicles using transmembrane domains from viral glycoproteins for enhanced immunogenicity - Kai Hu; Paul F. McKay; Karnyart Samnuan; Adrian Najer; Anna K. Blakney; Junyi Che; Gwen O'Driscoll; Martina Cihova; Molly M. Stevens; Robin J. Shattock (Journal of Extracellular Vesicles, 2022)
Abstract A vaccine antigen, when launched as DNA or RNA, can be presented in various forms, including intracellular, secreted, membrane‐bound, or on extracellular vesicles (EVs). Whether an antigen in one or more of these forms is superior in immune induction remains unclear. In this study, we used GFP as a model antigen and first compared the EV‐loading efficiency of transmembrane domains (TMs) from various viral glycoproteins, and then investigated whether EV‐bound GFP (EV‐GFP) would enhance immune induction. Our data showed that GFP fused to viral TMs was successfully loaded onto the surface of EVs. In addition, GFP‐bound EVs were predominantly associated with the exosome marker CD81. Immunogenicity study with EV‐GFP‐producing plasmids in mice demonstrated that antigen‐specific IgG and IgA were significantly increased in EV‐GFP groups, compared to soluble and intracellular GFP groups. Similarly, GFP‐specific T cell response‐related cytokines produced by antigen‐stimulated splenocytes were also enhanced in mice immunized with EV‐GFP constructs. Immunogenicity study with purified soluble GFP and GFP EVs further confirmed the immune enhancement property of EV‐GFP in mice. In vitro uptake assays indicated that EV‐GFP was more efficiently taken up than soluble GFP by mouse splenocytes and such uptake was B cell preferential. Taken together, our data indicate that viral TMs can efficiently load antigens onto the EV surface, and that EV‐bound antigen enhances both humoral and cell‐mediated antigen‐specific responses.